2000
DOI: 10.1038/sj.ejcn.1601111
|View full text |Cite
|
Sign up to set email alerts
|

A novel infant formula milk with added long-chain polyunsaturated fatty acids from single-cell sources: a study of growth, satisfaction and health

Abstract: Objective: To evaluate the growth, feeding and health of babies fed a novel infant formula milk with added long chain polyunsaturated fatty acids (LCPs) produced from single-cell sources, at concentrations similar to those found in mature breast milk. Design: Randomized double-blind control trial. Subjects: One-hundred and forty healthy, full-term infants of birth weight 2.5 ± 4.5 kg born at the Maternity Department, East Glamorgan General Hospital, Wales, whose mothers had already decided to bottle feed. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…In contrast to studies in preterm infants, no significant reductions in weight or length have been reported among groups of term infants fed formulas supplemented with egg lipid (26)(27)(28)(29), egg phospholipid and/or triglyceride (30)(31)(32)(33), various fish oils (31)(32)(33)(34)(35)(36)(37)(38), or single-cell sources of DHA and/or AA (33,39,40). One study, however, reported a significantly lower head circumference at 4 mon of age in infants fed a formula enriched with low-EPA fish oil vs. the unsupplemented formula (35).…”
Section: Pufa Intake and Growth In Term Infantsmentioning
confidence: 78%
See 2 more Smart Citations
“…In contrast to studies in preterm infants, no significant reductions in weight or length have been reported among groups of term infants fed formulas supplemented with egg lipid (26)(27)(28)(29), egg phospholipid and/or triglyceride (30)(31)(32)(33), various fish oils (31)(32)(33)(34)(35)(36)(37)(38), or single-cell sources of DHA and/or AA (33,39,40). One study, however, reported a significantly lower head circumference at 4 mon of age in infants fed a formula enriched with low-EPA fish oil vs. the unsupplemented formula (35).…”
Section: Pufa Intake and Growth In Term Infantsmentioning
confidence: 78%
“…One study, however, reported a significantly lower head circumference at 4 mon of age in infants fed a formula enriched with low-EPA fish oil vs. the unsupplemented formula (35). In addition, Morris et al (40) reported that the subscapular skinfold thickness of infants fed a formula enriched with single-cell oils (DHA + AA) was significantly lower than that of controls at both 6 wk and 3 mon of age. In addition, Morris et al (40) reported that the subscapular skinfold thickness of infants fed a formula enriched with single-cell oils (DHA + AA) was significantly lower than that of controls at both 6 wk and 3 mon of age.…”
Section: Pufa Intake and Growth In Term Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have examined effects on body composition. One study has reported that formula with LCPUFA resulted in a significant decrease in subscapular skinfold thickness in term infants at the age of 1.5 and 3 mo, but this was not evident at 6 and 12 mo and was not accompanied by lower triceps skinfold thickness (24).…”
Section: Effect Of Maternal Fish Oil On Child Bmimentioning
confidence: 99%
“…Durante los siete primeros 1910 pensaba que la leche de vaca era una opción de la leche humana, y que el pecho materno no era esencial para el lactante (Mepham, 1993;Sánchez et al, 2008). Desde entonces, se han visto muchos cambios en la alimentación del lactante, desde la mejora extraordinaria de las leches industrializadas y fórmulas modificadas, pasando por las grandes controversias sobre su uso en población con condiciones higiénicas deplorables, hasta el resurgimiento a partir de la década de los setenta de la alimentación con leche materna, que en la actualidad se considera insuperable por la gran cantidad de propiedades nutritivas, inmunológicas y psicoafectivas que hasta la fecha no han logrado las fórmulas lác-teas, ya que ha sido un verdadero reto para los productores de fórmulas infantiles diseñar y fabricar una fórmula que se acerque a los estándares de referencia de la alimentación infantil (Morris et al, 2000;Carver, 2003;Gil et al, 2006;Sánchez et al, 2008;Prosser et al, 2010;Martinez y Ballew, 2011).…”
Section: Composición De Las Leches Humana Y Vacaunclassified